THEORETICAL BASICS OF DEFINING HR-ENGINEERING OF THE ENTERPRISE (Development Service Industry Management, 2023)
The article examines the implementation of the HR engineering system at a modern enterprise. The main prerequisites of innovative approaches to personnel management with the involvement of motivational factors are considered. The relevance of this study occurs in the growing importance of the concept of HR management in modern society. Special emphasis is placed on its impact on the career management system of employees at enterprises and increasing labor productivity. This contributes to the improvement of staff motivation and expands the understanding of the effectiveness of employee career management and motivational measures at enterprises. The choice of specific personnel management strategies determines the impact on the performance of the enterprise and the prospects for its development in the future. Business leaders are increasingly faced with the importance of HR-management issues that ensure the effectiveness of human resources management directly on labor productivity and general performance indicators of the enterprise.The essence of the concept of "HR-engineering" is determined, which includes the totality of an effective system of personnel integration, corporate architecture and information technologies. An overview analysis of the impact on the content of engineering of the current principles of evaluating work results and the compensation system was carried out. The composition of business processes, which are expedient to implement for the implementation of the HR engineering system at a modern enterprise, has been determined. The main tasks, principles and stages of implementation of HR engineering at the enterprise are considered. For Ukrainian enterprises, engineering, in particular HR-engineering, is an urgent issue, since domestic enterprises need the implementation of new world-class technologies to change the management system and carry out production activities. Raising production to the international level will provide opportunities for a high level of organization of enterprises, their economic component and will ensure the sustainable development of our country and the growth of its well-being.The complex of works during the practical application of business process engineering principles at the enterprise is described in detail. The positive and negative consequences of the implementation of the business process engineering method are determined.
Keywords: HR engineering; HR management; HR technologies; business processes; personnel management